2007
DOI: 10.1007/978-3-540-77090-9_64
|View full text |Cite
|
Sign up to set email alerts
|

New Efficient Certificateless Signature Scheme

Abstract: Abstract. In ubiquitous computing environment, how to implement security and trust among the users that connected to a network is a big problem. Digital signature provides authenticity, integrity and nonrepudiation to many kinds of applications in ubiquitous computing environment. In this paper, we present a very efficient certificateless signature scheme from bilinear maps. In our scheme, only one paring operation is needed in the signing and verification processes. The security of the new scheme is based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Huang et al also proposed a new CLS scheme. Some relatively more efficient and secure CLS schemes [9,11,14] were proposed to overcome this high computational cost. However, because Hu et al [6] showed that their scheme cannot resist type 1 adversaries, Yum and Lee improved their scheme.…”
Section: Related Workmentioning
confidence: 99%
“…Huang et al also proposed a new CLS scheme. Some relatively more efficient and secure CLS schemes [9,11,14] were proposed to overcome this high computational cost. However, because Hu et al [6] showed that their scheme cannot resist type 1 adversaries, Yum and Lee improved their scheme.…”
Section: Related Workmentioning
confidence: 99%
“…Please refer to [1,8,11,13,14] for details. The two original schemes [4,5] are based on bilinear maps.…”
Section: Review Of the Original Schemesmentioning
confidence: 99%
“…Here we give two kinds of universal forgery under known message attacks. [1,4,5,8,11,13,14]. Let 蟽 = (S, R,V ) be ID's valid signature on a message M, where…”
Section: Universal Forgerymentioning
confidence: 99%
See 1 more Smart Citation
“…Several certificateless signature schemes(CLS) [3][4][5] have been proposed,since the certificateless public key cryptography appeared. However, most of the schemes are insecure and can be attack by a public key replacement.…”
Section: Introductionmentioning
confidence: 99%